2014
DOI: 10.1007/s10461-014-0873-1
|View full text |Cite
|
Sign up to set email alerts
|

Does Food Insecurity Undermine Adherence to Antiretroviral Therapy? A Systematic Review

Abstract: A growing body of research has identified food insecurity as a barrier to antiretroviral therapy (ART) adherence. We systematically reviewed and summarized the quantitative literature on food insecurity or food assistance and ART adherence. We identified nineteen analyses from eighteen distinct studies examining food insecurity and ART adherence. Of the thirteen studies that presented an adjusted effect estimate for the relationship between food insecurity and ART adherence, nine found a statistically signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
120
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 165 publications
(147 citation statements)
references
References 66 publications
11
120
1
2
Order By: Relevance
“…It was found to be directly associated with VAS adherence and pill counts. This is in agreement with numerous studies and a meta-analysis [46][47][48] which have reported an association between food insecurity and ART adherence. Food insecurity has been found to be associated with poor antiretroviral adherence among people living with HIV (PLHIV) [49].…”
Section: Discussionsupporting
confidence: 93%
“…It was found to be directly associated with VAS adherence and pill counts. This is in agreement with numerous studies and a meta-analysis [46][47][48] which have reported an association between food insecurity and ART adherence. Food insecurity has been found to be associated with poor antiretroviral adherence among people living with HIV (PLHIV) [49].…”
Section: Discussionsupporting
confidence: 93%
“…Our results have parallels to other literature demonstrating links between food insecurity, economic vulnerability, gendered power dynamics, and transactional sex or sex work (Chatterji, Murray, London, & Anglewicz, 2005;Cluver et al, 2012;Dunkle et al, 2007;Fielding-Miller, Mnisi, Adams, Baral, & Kennedy, 2014;Lwenya & Yongo, 2012;McCoy, Ralph, Njau, Msolla, & Padian, 2014;Robinson & Yeh, 2011). Further, these results position a gendered economy and environmental change as structural drivers of HIV, with parallels to other work on such drivers Govender, Seeley, & Watts, 2014;MacPherson et al, 2012) and the roles that persistent food insecurity and poverty play in perpetuating stigma (Tsai, Bangsberg, & Weiser, 2013) and undermining treatment adherence (Singer, Weiser, & McCoy, 2014;Weiser et al, 2014).…”
Section: Discussionsupporting
confidence: 86%
“…Both malnutrition and HIV impact immune system functioning and when these two conditions co-occur the impact on the immune system is compounded and synergistic [9]. In addition to the detrimental impacts that food insecurity has on the physical health of people living with HIV, food insecurity has also been associated with worse health behaviors, such as lower antiretroviral (ARV) medication adherence and higher levels of sexual risk behavior [10, 11]. …”
mentioning
confidence: 99%